Karuk Stories - Davis, Shan.; Bennett, Ruth; California State Univ.-Humboldt, Arcata. Center for Community Development ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Three illustrated stories from the Karuk Indians of northwestern California are told in free English translation and in Karuk with literal English translation. Stories tell of Bluejay who pretends to be sick to get higher pay for doctoring the person she is making sick, how the Karuk learned to kill the fattest deer, and the waterdog who kills the one he hates. (LFL)
Sponsoring Agency: Office of Bilingual Education and Minority Languages Affairs (ED), Washington, DC.
ERIC Note: For related document, see RC 016 276-282.
Educational level discussed: Adult Education.
Educational level discussed: Elementary Secondary Education.
Students.
May also be available online. Address as at 14/8/18
Keywords: Adult Education; American Indian Culture; American Indian Education; American Indian Languages; American Indians; Bilingual Instructional Materials; Cultural Background; Elementary Secondary Education; Legends; Native Language Instruction; Cultural Literacy -- Karuk; California -- Karuk (Tribe) -- UNIFON Alphabet; Creative Works; Historical Materials; Multilingual/Bilingual Materials